Retinopathy in Metabolic Dysfunction-Associated Steatotic Liver Disease - Myrsini Orfanidou; Stergios A. Polyzos (Medicina)
Metabolic dysfunction-associated steatotic liver disease (MASLD) is a multisystemic disease, i.e., influencing various organ systems beyond the liver and, thus, contributing to comorbidities. Characterized by excessive fat accumulation in the hepatocytes, MASLD is frequently linked to metabolic syndrome components, such as obesity, insulin resistance, dyslipidemia, and hypertension. Therefore, exploring the intricate connection between MASLD and other organ systems, including the eyes, seems to be essential. In this context, retinopathy has been investigated for its potential association with MASLD, since both conditions share common pathogenetic pathways. Chronic low-grade inflammation, oxidative stress, insulin resistance, and endothelial dysfunction are only some of those mechanisms contributing to disease progression and, possibly, determining the bidirectional interplay between the liver and retinal pathology. This narrative review aims to summarize data concerning the multisystemicity of MASLD, primarily focusing on its potential association with the eyes and, particularly, retinopathy. Identifying this possible association may emphasize the need for early screening and integrated management approaches that address the liver and eyes as interconnected components within the framework of a systemic disease. Further research is necessary to delineate the precise mechanisms and develop targeted interventions to mitigate the bidirectional impact between the liver and eyes, aiming to reduce the overall burden of disease and improve patient outcomes.